Development and Validation of Spectrophotometric Method for the Determination of Anti-HIV Drug - Rao Garikapati, Devala (Asian Journal of Chemistry, 2016)
A simple, sensitive and precise spectrophotometric method has been developed for the determination of one anti-HIV drug, lamivudine, in bulk and in its pharmaceutical formulations. Lamivudine gives blue coloured chromogen with phosphomolybdotungstic acid [Folin-Ciocalteu (FC) reagent] under alkaline conditions with an absorption maximum at 750 nm. The chromogen obeys Beer's law in the concentration range of 7.5–75 μg/mL. The proposed method is reproducible, statistically validated and recoveries range from 98.65 to 99.80%.